A Knight of the Cumberland - Fox, John, Jr., 1862-1919 (Salt Lake City, UT : Project Gutenberg, 2008)
"A Knight of the Cumberland" by John Fox, Jr. is a novel written during the early 20th century that immerses readers in the rugged beauty and culture of the Cumberland Mountains. The narrative focuses on the adventures of the main characters as they venture into the wilds of these Appalachian hills, exploring themes of innocence, social dynamics, and the clash between different cultures. Central to the story is a captivating character known as "the Blight," a young woman whose charm and grace captivate those around her, while her companions, including a narrator and a little sister, experience the intricacies of life in this isolated yet vibrant setting. At the start of the novel, we accompany the narrator, his sister, and the Blight as they traverse the rugged terrain of the Cumberland Mountains on a sunny October day. The journey is not just a physical one but also a passage into a world filled with colorful mountaineers, social tensions, and hints of feuds and moonshining. The narrator describes the Blight's enchanting presence, contrasting her sophistication with the ruggedness of the setting and the people they encounter. From moments of playful joy to encounters that reveal the darker side of hill life, the opening establishes a vivid backdrop where social class, charm, and danger intersect, setting the stage for the unfolding drama and adventures that lie ahead. (This is an automatically generated summary.)
Release date is 2008-07-09
Produced by Mike Lough, and David Widger
Keywords: Historical fiction; Country life -- Fiction; Kentucky -- Fiction